Impact of clinical exomes in neurodevelopmental and neurometabolic disorders - Evers, Christina; Staufner, Christian; Granzow, Martin; Paramasivam, Nagarajan; Hinderhofer, Katrin; Kaufmann, Lilian; Fischer, Christine; Thiel, Christian; Opladen, Thomas; Kotzaeridou, Urania; Eils, Roland; Kölker, Stefan; et al. (Molecular genetics and metabolism, 2017)
Whole exome sequencing (WES) is well established in research and is now being introduced into clinically indicated diagnostics (so-called clinical exomes). We evaluated the diagnostic yield and clinical implications of WES in 72 patients from 60 families with undiagnosed neurodevelopmental disorders (NDD), neurometabolic disorders, and dystonias. Pathogenic or likely pathogenic variants leading to a molecular diagnosis could be identified in 21 of the 60 families (overall 35%, in 36% of patients with NDD, in 43% of patients with neurometabolic disorders, in 25% of patients with dystonias). In one family two coexisting autosomal recessive diseases caused by homozygous pathogenic variants in two different genes were diagnosed. In another family, a homozygous frameshift variant in STRADA was found to cause a severe NDD with early onset epilepsy, brain anomalies, hypotonia, heart defect, nephrocalcinosis, macrocephaly and distinctive facies so far designated as PMSE (polyhydramnios, megalencephaly, symptomatic epilepsy) syndrome. In 7 of the 21 families with a molecular diagnosis the pathogenic variants were only identified by clinical follow-up, manual reevaluation of the literature, a change of filter setting, and/or reconsideration of inheritance pattern. Most importantly, clinical implications included management changes in 8 cases and impact on family planning in 20 families with a molecular diagnosis. This study shows that reevaluation and follow-up can improve the diagnostic rate and that WES results have important implications on medical management and family planning. Furthermore, we could confirm STRADA as a gene associated with syndromic ID but find it questionable if the current designation as PMSE depicts the most important clinical features.